Industrial Applications of Advanced Oxidation Technologies: Past and Future - Hodaifa, Gassan; Borja, Rafael; Albqmi, Mha (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The use of Advanced Oxidation Technologies (AOTs) for wastewater treatment is an important area of research which has not yet been fully exploited at an industrial level and has significant potential in the disposal of many industrial effluents. In particular, this includes effluents that are difficult to treat by conventional biological treatment processes. This reprint covers the latest advances in the field of wastewater treatment by Advanced Oxidation Technologies, with a focus on treatments based on photolysis, TiO2/solar light, ozone/ultraviolet irradiation, oxidant/ultraviolet irradiation, oxidant/catalyst/ultraviolet irradiation, high-energy electron beam irradiation (E-beam), sonication/photocatalysis, etc.